Management and conservation at the International Whaling Commission: A dichotomy sandwiched within a shifting baseline. (September 2017) - Galletti Vernazzani, B.; Burkhardt-Holm, P.; Cabrera, E.; Iñíguez, M.; Luna, F.; Parsons, E.C.M.; Ritter, F.; Rodríguez-Fonseca, J.; Sironi, M.; Stachowitsch, M.
Abstract: The International Whaling Commission's (IWC) Scientific Committee provides important advice to the IWC on a large variety of cetacean species, sub-species and populations and the issues affecting them. Cetaceans are facing increasing, non-whaling-related threats, and the Scientific Committee (SC), in accordance with the Commission's requests, has strengthened its conservation-oriented research work. A selection of the reports of the Scientific Committee from between 1986 and 2012 was assessed for its: (i) fundamental research; (ii) management; (iii) conservation; and (iv) administrative content, and to identify potential trends over time. Recommendations and their urgency were also examined, as implied from the language used by the SC in its reports. The analysis showed that the work of the Scientific Committee has increasingly been oriented towards conservation issues over the period reviewed, but at the same time this conservation work has received little funding. Increased support for conservation-related research projects is warranted to promote the long-term survival of cetaceans. Based on this review of the content and focus of the Committee reports, the analysis suggested that its issued advice be made clearer, whenever possible, and governments are urged to give due consideration to this science-based advice particularly when urgent conservation actions are needed. In addition, more consistent funding of the IWC's conservation-related research should be pursued to improve international conservation outputs regarding cetacean populations. Highlights: Statements in IWC Scientific Committee reports are used to track its evolution. Conservation-oriented research work has increased but still receives little funding. A dichotomy between conservation of cetaceans and management of whaling is found. Small Cetacean sub-committee greatly contributes to the conservation agenda. Lack of governmental effective management actions condemn several populations.